mescal: a tool for coupling energy system models with life-cycle assessment. - Souttre, Matthieu; Majeau-Bettez, Guillaume; Maréchal, François; Margni, Manuele (Journal of Industrial Ecology, 2026)
Energy system models are widely used to design and assess energy transition scenarios. Energy system models help decision-makers to project energy policies and understand their impact on strongly interconnected energy systems. However, energy system models typically lack a set of comprehensive environmental indicators beyond carbon emissions, which are essential to assess the sustainability of energy transition scenarios and minimize the risk of burden shifting. mescal is a Python package that integrates life-cycle assessment indicators in energy system models. mescal allows energy modelers to expand the scope of analysis, encompassing indirect impacts from the infrastructure, and to include a wider set of environmental indicators in a transparent and reproducible way. As a result, mescal enhances the capability of energy system models in supporting decision-making by providing a more comprehensive sustainability assessment, helping identify environmental hot spots and trade-offs in energy transition scenarios.